Dual-sided centripetal microgrooved poly (D,L-lactide-co-caprolactone) disk encased in immune-regulating hydrogels for enhanced bone regeneration - You Wu; Xiaokun Yue; Ying Zhang; Ning Yu; Chengyan Ge; Rui Liu; Zhongying Duan; Lilong Gao; Xinlong Zang; Xin Sun; Deteng Zhang (Materials Today Bio)
Well-designed artificial scaffolds are urgently needed due to the limited self-repair capacity of bone, which hampers effective regeneration in critical defects. Optimal scaffolds must provide physical guidance to recruit cells and immune regulation to improve the regenerative microenvironment. This study presents a novel scaffold composed of dual-sided centripetal microgrooved poly(D,L-lactide-co-caprolactone) (PLCL) film combined with a dynamic hydrogel containing prednisolone (PLS)-loaded Prussian blue nanoparticles (PB@PLS). The microgrooves on the surface of the PLCL film were imprinted using a micropatterned polydimethylsiloxane (PDMS) template. Following aminolysis, the PLCL film was covalently grafted with the EM-7 peptide via glutaraldehyde. Functional group analysis, surface morphology and hydrophilicity were evaluated using X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), and an optical contact angle measuring instrument, respectively. Bone regeneration-related cells (e.g., bone marrow mesenchymal stem cells, macrophages, Schwann cells, and endothelial cells) cultured on PLCL films tended to align along the stripes and migrate from the periphery toward the center region in vitro. Subsequently, the PLCL film was encapsulated in an immune-regulating hydrogel synthesized from thiol-modified gelatin and Cu2+ in the presence of PB@PLS nanoparticles, which demonstrated excellent antioxidant properties. This scaffold significantly accelerated critical-sized bone regeneration, as evidenced by an increase in the volume of newly formed bone and histological images in vivo. This innovative approach holds substantial promise for clinical applications in bone regeneration and broader tissue repair.